2022
DOI: 10.1039/d1gc04694b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic dissolution of metals from printed circuit boards using a calcium chloride–based deep eutectic solvent

Abstract: Due to their high metal content, printed circuit board (PCBs) are an attractive resource for metal recovery. Until now, the dissolution and subsequent recovery of metals from PCBs considers either...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…Etch rates of up to 27 μm h −1 and 73 μm h −1 were measured for copper etching at 25 and 50 °C respectively using 1 mol kg −1 Cu II in a calcium chloride ethylene glycol eutectic. 4 Similar etch rates were also determined for gold using iodine in the EG : ChCl system. 10 In the present study the effect of water in the EG : ChCl system was studied and found to have a significant impact on the etching rates of copper, nickel, silver and gold.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Etch rates of up to 27 μm h −1 and 73 μm h −1 were measured for copper etching at 25 and 50 °C respectively using 1 mol kg −1 Cu II in a calcium chloride ethylene glycol eutectic. 4 Similar etch rates were also determined for gold using iodine in the EG : ChCl system. 10 In the present study the effect of water in the EG : ChCl system was studied and found to have a significant impact on the etching rates of copper, nickel, silver and gold.…”
Section: Resultsmentioning
confidence: 73%
“…Each individual gold rectangle is 2.5 × 1 mm, and is composed of 47 μm copper, 7 μm nickel, and 0.75 μm gold. 4…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Recently, systems formed from calcium chloride hexahydrate and ethylene glycol have been investigated, and remarkably, were found to have similar physicochemical properties to a DES formed from choline chloride and ethylene glycol. 33,34 In each of the solvent compositions investigated, copper, cobalt, and iron chloride complexes were present, despite the significant proportion of water in these systems – ranging from 17.5 to 24 kg mol −1 . This behaviour was proposed to be due to the water and ethylene glycol molecules being tightly solvated to the calcium cation.…”
Section: Introductionmentioning
confidence: 98%
“…The most commonly investigated systems have been quaternary ammonium salts with hydrogen bond donors (HBD) such as urea, ethylene glycol and glycerol 40 . The utilisation of inorganic chloride salts-based DESs have also been investigated [41][42][43][44] , which opens the opportunity to synthesise novel DESs by utilising in space materials. The presence of calcium, aluminium, iron, and zinc, for instance, have already been reported in regolith 4,25,45 , whereas the presence of halogen gas (chlorine, bromide) have been reported in the atmosphere of some planets like Mars and Venus 46 .…”
Section: Introductionmentioning
confidence: 99%